R factors in coliform-fecal coliform sewage flora of the prairies and Northwest Territories of Canada. - Bell, J B (1981)
Coliform and fecal coliform populations found in the raw sewages and final sewage effluents of the prairie provinces and the Northwest Territories were examined for antibiotic resistance and the possession of R factors. It was determined that 8.91% of the total coliform and 10.80% of the fecal coliform populations carried R factors. The following numbers of combinations of R determinants were found: 39 in the Escherichia coli population, 6 in the Citrobacter population, 20 in the Enterobacter populations, 10 in the Klebsiella populations, and 11 in the Aeromonas populations. The maximum number of R determinants transferable simultaneously was seven; organisms with R factors containing determinants for chloramphenicol usually contained determinants for ampicillin. Of the coliform and fecal coliform populations, 2 to 4% were resistant to chloramphenicol in some provinces, and from 17 to 30% of the populations were resistant to three or more antibiotics. It was calculated that coliforms containing R factors in the raw sewage reached population levels of 1.5 X 10(7)/100 ml, and fecal coliforms containing R factors reached population levels of 8.6 X 10(5) ml. Final effluent discharges to the receiving environment contained R factor-containing coliform and fecal coliform populations of 3.1 X 10(4)/100 ml and 5.8 X 10(2)/100 ml, respectively. The incidence of bacteria containing R factors in sewage appears to be increasing with time, and their removal from sewage before discharge to the receiving environment is desirable. Consideration of data on bacteria with R factors should be made in future water quality deliberations and in discharge regulations.